The role of social networking sites in support library Activitiescentralat Al-Mustansiriya University - Sabah, Layla Hassan (Edelweiss Applied Science and Technology, 2024)
The study aims to identify social networking sites in administrative work in the Central Library of Al-Mustansiriya University and to identify the problem of the lack of use of social networking applications and its impact on the exchange of information and management efficiency. The study followed the survey method and reviewed these sites. The questionnaire was used as a tool for collecting data with a sample consisting of employees in the Central Library of Al-Mutessarifat University. The research sample included 35 employees. The questionnaire was distributed to them in order to obtain their opinions regarding the evaluation of social networking sites in the Central Library. The first chapter included the study methodology. The second chapter also focused on the theoretical framework that was obtained from various information sources. The third chapter, which is the practical aspect of the study, came through implementing statistical operations and analyzing their results. The fourth chapter was devoted to the results and recommendations. It was reached Several results, the most important of which are: 1- One of the most prominent social networking sites that the library uses is Facebook. 2- It was found through the study sample that there is no Internet network in the central library and that employees use the Internet at their own expense. The researcher made several recommendations, the most prominent of which are: 1- Improving the use of social media in promoting library services. 2- Enhancing the use of social media to connect library workers.